A qualitative study of community elders' perceptions about the underutilization of formal maternal care and maternal death in rural Nigeria - Arone Wondwossen Fantaye; Friday Okonofua; Lorretta Ntoimo; Sanni Yaya (BMC, 2019)
Abstract Background Underutilization of formal maternal care services and accredited health attendants is a major contributor to the high maternal mortality rates in rural communities in Nigeria. Perceptions of a poor quality of care and inaccessible services in health facilities strongly influence the low use of formal maternal care services. There is therefore a need to understand local perceptions about maternal health services utilization and maternal death. This study thereby aims to explore perceptions and beliefs about the underutilization of formal care and causes of maternal death, as well as to identify potential solutions to improve use and reduce maternal mortality in rural Nigeria. Methods Data were collected through 9 community conversations, which were conducted with 158 community elders in 9 rural communities in Edo State, Nigeria. Data from transcripts were analyzed through inductive thematic analysis using NVivo 12 software. Results Perceived reasons for the underutilization of formal maternal care included poor qualities of care, physical inaccessibility, financial inaccessibility, and lack of community knowledge. Perceived reasons for maternal death were related to medical causes, maternal healthcare services deficiencies, uptake of native maternal care, and poor community awareness and negligence. Elders identified increased access to adequate maternal care, health promotion and education, community support, and supernatural assistance from a deity as solutions for increasing use of formal maternal care and reducing maternal mortality rates. Conclusion Study results revealed that multifaceted approaches that consider community contexts, challenges, and needs are required to develop acceptable, effective and long-lasting positive changes. Interventions aiming to increase use of formal care services and curb maternal mortality rates must target improvements to the technical and interpersonal qualities of care, ease of access, community awareness and knowledge, and allow community members to actively engage in implementation phases.